Silk fibroin / sodium hyaluronate composite microsphere gel as well as preparation method and application thereof
By preparing silk fibroin/sodium hyaluronate composite microsphere gel, the problem of rapid degradation and poor stability of existing dermal fillers is solved, and higher stability and heat resistance is achieved. Injections or gel dressings suitable for cosmetic and medical purposes are suitable for injections or gel dressings.
Patent Information
- Application Number
- CN202411892456.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
Existing dermal fillers such as sodium hyaluronate gel and silk fibroin microspheres have problems such as rapid degradation, poor stability and inconvenience in use, especially after sterilization, the microspheres are prone to agglomeration and precipitation, which affects the use of the product.
The preparation method of silk fibroin/sodium hyaluronate composite microsphere gel is adopted. By mixing sodium hyaluronate solution, silk fibroin solution and organic solvent, freeze and crystallize, spray-drying to form composite microspheres, and a stable gel structure is formed through cross-linking reaction, improving the heat resistance and stability of the material.
The prepared silk fibroin/sodium hyaluronate composite microsphere gel has higher stability and heat resistance, avoiding the problems of precipitation and aggregation of microspheres during use, and is easy to inject as an injection, and is suitable for cosmetic and medical purposes.
Smart Images

Figure CN119751919A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable polymer biomaterials, and in particular to a silk fibroin / sodium hyaluronate composite microsphere gel and a preparation method and application thereof. Background Art
[0002] Sodium hyaluronate is an inherent component in the dermis of human skin. It has good biocompatibility and degradability, and is an ideal natural moisturizing material. It has been widely used in the fields of biomedicine and tissue engineering. Silk fibroin has also begun clinical applications due to its excellent biocompatibility and low immunogenicity. Currently, there are also silk fibroin products on the market, such as silk fibroin membrane dressings (National Medical Device Registration No. 20203140593).
[0003] At present, there are many materials that can be used for skin fillers, such as sodium hyaluronate gel, polycaprolactone microspheres, poly-L-lactic acid microspheres, silk fibroin microspheres, etc., but there are still various problems that need to be solved. For example, pure sodium hyaluronate gel is only suitable for filling and hydrating skin tissue, and the material needs to be implanted again after rapid degradation. Microsphere products are either freeze-dried into powder and need to be compounded when used, or the microsphere solution tends to become unstable after sterilization. For example, silk fibroin microspheres can promote cell proliferation in the filling area as a tissue filling material and have the function of nourishing tissues, but silk fibroin microspheres are prone to agglomeration, precipitation, and inability to be injected from the injection needle after sterilization. They have poor heat resistance and stability, which affects the use of the product. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a preparation method and application of a silk fibroin / sodium hyaluronate composite microsphere gel. The silk fibroin / sodium hyaluronate composite microsphere gel prepared by the present invention has good heat resistance and structural stability, and has a slow degradation rate, and can be applied to injections or gel dressings for cosmetic and medical purposes.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a silk fibroin / sodium hyaluronate composite microsphere gel, comprising the following steps: mixing a sodium hyaluronate solution, a silk fibroin solution and an organic solvent, freezing and crystallizing the obtained mixed solution and then thawing it to obtain a silk fibroin / sodium hyaluronate composite emulsion;
[0007] spray-drying the silk fibroin / sodium hyaluronate composite emulsion to obtain silk fibroin / sodium hyaluronate composite microspheres;
[0008] The silk fibroin / sodium hyaluronate composite microspheres, sodium hyaluronate powder and alkaline solution are mixed until the sodium hyaluronate powder is completely dissolved to obtain a dissolved liquid; the dissolved liquid is mixed with a cross-linking agent to perform a cross-linking reaction to form a gel;
[0009] The gel is placed in water for swelling, and then taken out and placed in a buffer solution for shrinkage and strengthening to obtain the silk fibroin / sodium hyaluronate composite microsphere gel.
[0010] Preferably, after obtaining the silk fibroin / sodium hyaluronate composite microsphere gel, the method further comprises sterilizing the silk fibroin / sodium hyaluronate composite microsphere gel to obtain a sterile silk fibroin / sodium hyaluronate composite microsphere gel.
[0011] Preferably, the mass ratio of silk fibroin to sodium hyaluronate in the mixed solution is (3-7):1.
[0012] Preferably, the freezing crystallization temperature is -80 to -15°C, and the freezing crystallization time is 12 to 48 hours.
[0013] Preferably, the spray drying conditions include: an air inlet temperature of 100 to 200° C., a feed rate of 5 to 30 mL / min, and a fan frequency of 10 to 25 Hz.
[0014] Preferably, the mass ratio of the silk fibroin / sodium hyaluronate composite microspheres to the sodium hyaluronate powder is 1:(1.5-3);
[0015] The concentration of the silk fibroin / sodium hyaluronate composite microspheres in the dissolving solution is 20-50 mg / mL;
[0016] The mass concentration of alkali in the alkali solution is 0.01-2%;
[0017] The alkali in the alkali solution is sodium hydroxide and / or potassium hydroxide.
[0018] Preferably, the cross-linking agent includes 1,4-butanediol diglycidyl ether; the mass of the cross-linking agent is 0.1 to 5% of the mass of the dissolved liquid;
[0019] The temperature of the cross-linking reaction is 37-65° C. and the time is 6-24 hours.
[0020] Preferably, the buffer solution is a phosphate buffer solution or a sodium chloride solution, and the osmotic pressure of the buffer solution is 300 to 400 mOsmol / kg.
[0021] The present invention provides a silk fibroin / sodium hyaluronate composite microsphere gel prepared by the preparation method described in the above scheme, comprising a sodium hyaluronate gel and silk fibroin / sodium hyaluronate composite microspheres cross-linked and distributed in the sodium hyaluronate gel.
[0022] The present invention provides the use of the silk fibroin / sodium hyaluronate composite microsphere gel described in the above scheme in the preparation of injections or gel dressings for cosmetic and medical purposes.
[0023] The invention provides a preparation method of a silk fibroin / sodium hyaluronate composite microsphere gel, comprising the following steps: mixing a sodium hyaluronate solution, a silk fibroin solution and an organic solvent, freezing and crystallizing the obtained mixed solution and then thawing it to obtain a silk fibroin / sodium hyaluronate composite emulsion; spray-drying the silk fibroin / sodium hyaluronate composite emulsion to obtain a silk fibroin / sodium hyaluronate composite microsphere; mixing the silk fibroin / sodium hyaluronate composite microsphere, sodium hyaluronate powder and an alkali solution until the sodium hyaluronate powder is completely dissolved to obtain a dissolved material solution; mixing the dissolved material solution and a cross-linking agent to perform a cross-linking reaction to form a gel; placing the gel in pure water for swelling, then taking it out and placing it in a buffer solution for shrinkage and strengthening to obtain the silk fibroin / sodium hyaluronate composite microsphere gel.
[0024] The present invention first prepares silk fibroin / sodium hyaluronate composite microspheres, and then cross-links with sodium hyaluronate gel to obtain silk fibroin / sodium hyaluronate composite microsphere gel. The silk fibroin / sodium hyaluronate composite microspheres have higher stability and heat resistance than single pure substance microspheres. At the same time, microspheres containing sodium hyaluronate components are also easier to be evenly dispersed in the sodium hyaluronate gel. Stable cross-linking points are formed between the composite microspheres and the sodium hyaluronate, so that even large-diameter microspheres will not precipitate or aggregate in the system. The ball-gel cross-linking system is more stable, has better mechanical properties, and is easy to store for a long time.
[0025] The silk fibroin / sodium hyaluronate composite microsphere gel of the present invention can still maintain good stability after high-temperature sterilization, does not have precipitation accumulation, is evenly dispersed, and is easy to push when used as an injection.
[0026] The preparation method of the silk fibroin / sodium hyaluronate composite microsphere gel provided by the present invention only uses two polymer materials, sodium hyaluronate and silk fibroin, and auxiliary materials such as organic solvents, alkali solutions and cross-linking agents added in the production process are also effectively removed in the process. The prepared silk fibroin / sodium hyaluronate composite microsphere gel has good biocompatibility, and through freezing crystallization, the silk fibroin undergoes β-folding, thereby slowing down the degradation rate in the body.
[0027] The preparation method of the silk fibroin / sodium hyaluronate composite microsphere gel provided by the present invention adopts the methods of material compounding, freeze crystallization, spray drying and ball-gel combination to form the silk fibroin / sodium hyaluronate composite microsphere gel, which has simple process, strong controllability, high yield, and controllable particle size of the prepared composite microspheres. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron micrograph of the silk fibroin / sodium hyaluronate composite microspheres prepared in Example 1;
[0029] Figure 2 This is a scanning electron microscope image of the silk fibroin / sodium hyaluronate composite microspheres prepared in Example 1 magnified 12,000 times;
[0030] Figure 3 This is a particle size distribution diagram of the silk fibroin / sodium hyaluronate composite microspheres prepared in Example 1;
[0031] Figure 4 This is the enzymatic degradation diagram of the silk fibroin / sodium hyaluronate composite microsphere gel prepared in Example 2;
[0032] Figure 5 The stability test results of Example 3 (B) and Control Example (A) are shown. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a silk fibroin / sodium hyaluronate composite microsphere gel, comprising the following steps: mixing a sodium hyaluronate solution, a silk fibroin solution and an organic solvent, freezing and crystallizing the obtained mixed solution and then thawing it to obtain a silk fibroin / sodium hyaluronate composite emulsion;
[0034] spray-drying the silk fibroin / sodium hyaluronate composite emulsion to obtain silk fibroin / sodium hyaluronate composite microspheres;
[0035] The silk fibroin / sodium hyaluronate composite microspheres, sodium hyaluronate powder and alkaline solution are mixed until the sodium hyaluronate powder is completely dissolved to obtain a dissolved liquid; the dissolved liquid is mixed with a cross-linking agent to perform a cross-linking reaction to form a gel;
[0036] The gel is placed in water for swelling, and then taken out and placed in a buffer solution for shrinkage and strengthening to obtain the silk fibroin / sodium hyaluronate composite microsphere gel.
[0037] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0038] The invention mixes a sodium hyaluronate solution, a silk fibroin solution and an organic solvent, freezes and crystallizes the obtained mixed solution and then thaws it to obtain a silk fibroin / sodium hyaluronate composite emulsion.
[0039] In the present invention, the concentration of the sodium hyaluronate solution is preferably 1-10 mg / mL. In a specific embodiment, the concentration of the sodium hyaluronate solution can be 2 mg / mL, 4 mg / mL, 5 mg / mL, 8 mg / mL or 10 mg / mL; the average molecular weight of the sodium hyaluronate is preferably 1200-1500 kDa. In a specific embodiment, the average molecular weight of the sodium hyaluronate can be 1200 kDa, 1300 kDa, 1400 kDa or 1500 kDa. In the present invention, the solvent of the sodium hyaluronate solution is water. Sodium hyaluronate is a glycosaminoglycan, an inherent component in the dermis of human skin, has good biocompatibility and degradability, and is an ideal natural moisturizing material. Its super strong water-locking effect can improve the water storage capacity of the skin and prevent skin aging. Its application in the fields of biomedicine, biomaterials, functional foods and cosmetics has been widely recognized and popular.
[0040] In the present invention, the concentration of the silk fibroin solution is preferably 5-50 mg / mL. In a specific embodiment, the concentration of the silk fibroin solution can be 5 mg / mL, 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL or 50 mg / mL; the average molecular weight of the silk fibroin is 20-200 kDa. In a specific embodiment, the average molecular weight of the silk fibroin can be 20 kDa, 50 kDa, 100 kDa, 150 kDa or 200 kDa. Silk fibroin is derived from silk and is a natural polymer protein material with excellent biocompatibility, good low immunogenicity, and biodegradable in vivo. Silk fibroin can be prepared into various forms of materials, which can be used as tissue repair materials when implanted in organisms, and slowly degraded into amino acids, providing nutrition for cell growth, promoting cell proliferation, and finally degraded into CO2 and H2O and discharged from the body.
[0041] In the present invention, the organic solvent is preferably an alcohol solvent, and the alcohol solvent preferably includes one or more of methanol, ethanol, propanol and isopropanol; the volume ratio of the total volume of the mixed solution of silk fibroin solution and sodium hyaluronate to the volume of the organic solvent is preferably (2-25):1, and in specific embodiments, it can be 2:1, 5:1, 10:1, 15:1 or 20:1.
[0042] In the present invention, the mixing is preferably: firstly mixing the sodium hyaluronate solution with the silk fibroin solution, and then adding an organic solvent to mix to obtain a mixed solution.
[0043] In the present invention, the mass ratio of silk fibroin to sodium hyaluronate in the mixed solution is preferably (3-7):1. In specific embodiments, it can be 3:1, 4:1, 5:1, 6:1 or 7:1.
[0044] In the present invention, the temperature of the frozen crystallization is preferably -80 to -15°C, and the time of the frozen crystallization is preferably 12 to 48 hours; in a specific embodiment, the temperature of the frozen crystallization can be -80°C, -70°C, -60°C, -50°C, -40°C, -30°C, -20°C or -15°C; the time of the frozen crystallization can be 12 hours, 24 hours, 28 hours, 36 hours or 48 hours. The present invention causes the silk fibroin to undergo a β-folding conformational change through frozen crystallization, and wraps the sodium hyaluronate in the formed particles. The present invention can control the β-folding degree of the silk fibroin by controlling the temperature and time of the frozen crystallization, thereby achieving the purpose of regulating the degradation rate.
[0045] In addition, the present invention can also adjust the particle size of the silk fibroin / sodium hyaluronate composite microspheres by regulating the volume ratio of the mixed solution of silk fibroin and sodium hyaluronate to the organic solvent and controlling the freezing temperature.
[0046] In the present invention, the thawing preferably includes: first placing at -4 to 25°C for 6 to 24 hours, and if it is not completely thawed, continuing to place at room temperature until it is completely thawed.
[0047] After obtaining the silk fibroin / sodium hyaluronate composite emulsion, the present invention spray-dries the silk fibroin / sodium hyaluronate composite emulsion to obtain silk fibroin / sodium hyaluronate composite microspheres.
[0048] Before the spray drying, the present invention preferably dilutes the silk fibroin / sodium hyaluronate composite emulsion with pure water, and the dilution multiple is preferably 1 to 10 times. In a specific embodiment, it can be diluted 2 times, 4 times, 5 times, 7 times or 10 times, which will not be enumerated here.
[0049] In the present invention, the conditions for spray drying include: the inlet air temperature is preferably 100-200°C, the feed rate is preferably 5-30mL / min, and the fan frequency is preferably 10-25Hz; in a specific embodiment, the inlet air temperature can be 100°C, 120°C, 140°C, 160°C, 180°C or 200°C; the feed rate can be 5mL / min, 10mL / min, 15mL / min, 20mL / min, 25mL / min or 30mL / min; the fan frequency can be 10Hz, 15Hz, 20Hz or 25Hz.
[0050] In the present invention, the particle size of the silk fibroin / sodium hyaluronate composite microspheres is preferably 100 nm to 10 μm.
[0051] After obtaining the silk fibroin / sodium hyaluronate composite microspheres, the present invention mixes the silk fibroin / sodium hyaluronate composite microspheres, sodium hyaluronate powder and alkali solution until the sodium hyaluronate powder is completely dissolved to obtain a dissolved liquid; the dissolved liquid is mixed with a cross-linking agent to perform a cross-linking reaction to form a gel.
[0052] In the present invention, the mass ratio of the silk fibroin / sodium hyaluronate composite microspheres to the sodium hyaluronate powder is preferably 1:(1.5-3). In a specific embodiment, the mass ratio of the silk fibroin / sodium hyaluronate composite microspheres to the sodium hyaluronate powder can be 1:1.5, 1:1.67, 1:2, 1:2.5, 1:2.67 or 1:3.
[0053] In the present invention, the alkali in the alkali solution is preferably sodium hydroxide and / or potassium hydroxide; the mass concentration of the alkali in the alkali solution is preferably 0.01-2%. In a specific embodiment, the mass concentration of the alkali in the alkali solution can be 0.01%, 0.05%, 0.1%, 0.5%, 1.0%, 1.5% or 2%.
[0054] The present invention utilizes alkaline solution to dissolve sodium hyaluronate powder, while the silk fibroin / sodium hyaluronate composite microspheres are not dissolved.
[0055] In the present invention, the concentration of the silk fibroin / sodium hyaluronate composite microspheres in the dissolving solution is preferably 20-50 mg / mL. In specific embodiments, it can be 20 mg / mL, 25 mg / mL, 30 mg / mL, 35 mg / mL, 40 mg / mL, 45 mg / mL or 50 mg / mL.
[0056] In the present invention, the cross-linking agent preferably includes 1,4-butanediol diglycidyl ether; the mass of the cross-linking agent is preferably 0.1-5% of the mass of the dissolved liquid. In a specific embodiment, the mass of the cross-linking agent can be 0.1%, 0.5%, 1.0%, 1.5%, 2%, 3%, 3.5%, 4.0%, 4.5% or 5% of the mass of the dissolved liquid.
[0057] In the present invention, the temperature of the cross-linking reaction is preferably 37-65°C, and the time is preferably 6-24h; in a specific embodiment, the temperature of the cross-linking reaction can be 37°C, 40°C, 45°C, 50°C, 55°C, 60°C or 65°C; the time of the cross-linking reaction can be 6h, 10h, 15h, 20h or 24h.
[0058] In the cross-linking reaction process of the present invention, the sodium hyaluronate in the silk fibroin / sodium hyaluronate composite microspheres and the hydroxyl groups between the sodium hyaluronate molecules added later are cross-linked to form a network substance.
[0059] After obtaining the gel, the present invention places the gel in water for swelling, then takes it out and places it in a buffer solution for shrinkage and strengthening, thereby obtaining the silk fibroin / sodium hyaluronate composite microsphere gel.
[0060] In the present invention, the water is preferably pure water; the number of swellings is preferably 2 to 4 times, more preferably 3 times; the time for each swelling is preferably 3 to 15 hours, and in a specific embodiment, the time for each swelling can be 3 hours, 5 hours, 8 hours, 10 hours, 12 hours or 15 hours; the mass of water used for each swelling is preferably 20 to 50 times the mass of the gel, and in a specific embodiment, it can be 20 times, 30 times, 40 times or 50 times. The present invention can improve the performance of the gel through swelling, obtain better elasticity and toughness, and the swelling degree of the swollen silk fibroin / sodium hyaluronate composite microsphere gel is reduced, and the degradation rate can be slowed down when used.
[0061] In the present invention, the buffer is preferably a phosphate buffer or a sodium chloride solution, and the osmotic pressure of the buffer is preferably 300-400mOsmol / kg. In a specific embodiment, the osmotic pressure of the buffer may be 300mOsmol / kg, 320mOsmol / kg, 350mOsmol / kg, 370mOsmol / kg or 400mOsmol / kg. In the present invention, the number of contraction enhancement is preferably 2-4 times, more preferably 3 times; the time of each contraction enhancement is preferably 6-15h, in a specific embodiment, the time of each contraction enhancement may be 6h, 8h, 10h, 12h or 15h. The mass of the buffer used for each contraction enhancement is preferably 15-30 times the mass of the gel, in a specific embodiment, it may be 15 times, 20 times, 25 times or 30 times. The present invention increases the osmotic pressure of the gel by contraction enhancement to avoid swelling when implanted into the human body.
[0062] The present invention preferably sieves the contraction-strengthened silk fibroin / sodium hyaluronate composite microsphere gel into small gel particles, and then fills them into a prefilled syringe for standby use. In the present invention, the aperture of the sieve used for sieving is preferably 50 to 300 μm, and in a specific embodiment, it can be 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 250 μm or 300 μm.
[0063] In the present invention, the silk fibroin / sodium hyaluronate composite microsphere gel obtained by the above steps has not been sterilized. The present invention preferably further comprises sterilizing the silk fibroin / sodium hyaluronate composite microsphere gel to obtain a sterile silk fibroin / sodium hyaluronate composite microsphere gel.
[0064] In the present invention, the sterilization is preferably moist heat sterilization, the sterilization temperature is preferably 110 to 135° C., and the sterilization time is preferably 8 to 35 minutes.
[0065] The preparation method of the silk fibroin / sodium hyaluronate composite microsphere gel provided by the present invention adopts the methods of material compounding, freeze crystallization, spray drying and ball-gel combination to form the silk fibroin / sodium hyaluronate composite microsphere gel, which has simple process, strong controllability, high yield, and controllable particle size of the prepared composite microspheres.
[0066] The present invention provides a silk fibroin / sodium hyaluronate composite microsphere gel prepared by the preparation method described in the above scheme, comprising a sodium hyaluronate gel and a silk fibroin / sodium hyaluronate composite microsphere cross-linked and distributed in the sodium hyaluronate gel. In the present invention, the particle size of the silk fibroin / sodium hyaluronate composite microsphere is preferably 100nm to 10μm.
[0067] Silk fibroin / sodium hyaluronate composite microspheres have higher stability and heat resistance than single pure substance microspheres. At the same time, microspheres containing sodium hyaluronate components are also easier to disperse evenly in the sodium hyaluronate gel. Stable cross-linking points are formed between the composite microspheres and sodium hyaluronate. Even large-size microspheres will not precipitate or aggregate in the system. The ball-gel cross-linking system is more stable, has better mechanical properties, and is easy to preserve for a long time.
[0068] The silk fibroin / sodium hyaluronate composite microsphere gel of the present invention can still maintain good stability after high-temperature sterilization, does not have precipitation accumulation, is evenly dispersed, and is easy to push when used as an injection.
[0069] The present invention provides the use of the silk fibroin / sodium hyaluronate composite microsphere gel described in the above scheme in the preparation of injections or gel dressings for cosmetic and medical purposes.
[0070] The silk fibroin / sodium hyaluronate composite microsphere gel provided by the present invention and its preparation method and application are described in detail below in conjunction with the examples, but they should not be construed as limiting the scope of protection of the present invention.
[0071] Example 1
[0072] The preparation steps of silk fibroin / sodium hyaluronate composite microspheres are as follows:
[0073] (1) Preparation of silk fibroin / sodium hyaluronate composite emulsion:
[0074] Prepare 500 mL of a mixed solution of silk fibroin (average molecular weight of about 150 kDa) and sodium hyaluronate (average molecular weight of about 1200 kDa) (the mixed solution contains 15 g of silk fibroin and 2.5 g of sodium hyaluronate), then add 50 mL of ethanol solution, mix well and place it in a -23°C environment for freezing and crystallization for 24 hours. After the freezing treatment, place it at 0°C for 24 hours, and then thaw it at room temperature to obtain a milky white silk fibroin / sodium hyaluronate composite emulsion.
[0075] (2) Preparation of silk fibroin / sodium hyaluronate composite microspheres:
[0076] The composite emulsion was diluted 4 times with pure water, and then the composite microspheres were prepared by spray drying (spray drying parameters were: air inlet temperature 150°C, liquid feed rate 10mL / min, fan frequency 15Hz). The high temperature can effectively remove the diluted organic solvent ethanol, and collect pure and dry silk fibroin / sodium hyaluronate composite microspheres.
[0077] Microscopic morphology characterization of silk fibroin / sodium hyaluronate composite microspheres:
[0078] The silk fibroin / sodium hyaluronate composite microspheres prepared in step (2) of Example 1 were observed by scanning electron microscopy, and the overall appearance of the microspheres can be clearly observed. The microspheres are round, with regular and clearly visible outlines, and the boundaries between the microspheres are clear and uniform (see Figure 1 ). Magnify the microspheres by about 10,000 times and observe (see Figure 2 ), the surface of the microspheres is regular and has no edges or corners.
[0079] Particle size analysis of silk fibroin / sodium hyaluronate composite microspheres:
[0080] The silk fibroin / sodium hyaluronate composite microspheres prepared in step (2) of Example 1 were dispersed in pure water and then analyzed by a laser particle size analyzer. The light intensity of microspheres with a particle size of 1 to 6 μm accounted for about 83%. Figure 3 .
[0081] (3) Preparation of silk fibroin / sodium hyaluronate composite microsphere gel:
[0082] The silk fibroin / sodium hyaluronate composite microspheres and sodium hyaluronate powder were dissolved in a sodium hydroxide solution with a mass concentration of 0.5% (the concentration of the silk fibroin / sodium hyaluronate composite microspheres was 20 mg / mL and the concentration of sodium hyaluronate was 50 mg / mL) to obtain a dissolving liquid, and then 3wt% of 1,4-butanediol diglycidyl ether was added to the dissolving liquid, and the solution was stirred evenly and placed in a constant temperature environment of 55°C for cross-linking reaction for 8 hours to finally form a gel. The gel was placed in pure water for swelling 3 times, each time the amount of pure water was 40 times the mass of the gel, and each swelling time was 6 hours; then the swollen gel was placed in a sodium chloride solution with an osmotic pressure of 330mOsmol / kg for contraction and strengthening 3 times, each time the amount of sodium chloride solution was 40 times the mass of the gel, and each strengthening time was 10 hours.
[0083] (4) Preparation of sterile silk fibroin / sodium hyaluronate composite microsphere gel:
[0084] The silk fibroin / sodium hyaluronate composite microsphere gel after strengthening was sieved with a 20 μm pore size sieve, then filled into a prefilled syringe through a filling device, and then sterilized with wet heat at 121° C. for 12 minutes to obtain a sterile silk fibroin microsphere / sodium hyaluronate composite microsphere gel.
[0085] Example 2
[0086] Silk fibroin / sodium hyaluronate composite microsphere gel, the steps are as follows:
[0087] (1) Preparation of silk fibroin / sodium hyaluronate composite emulsion:
[0088] Prepare 500 mL of a mixed solution of silk fibroin (average molecular weight of about 20 kDa) and sodium hyaluronate (average molecular weight of about 1400 kDa) (the mixed solution contains 10 g of silk fibroin and 2 g of sodium hyaluronate), then add 100 mL of a mixed solution of ethanol and isopropanol (the volume ratio of ethanol to isopropanol is 1:1), mix well and place it in a -20°C environment for freezing and crystallization for 48 hours. After the freezing treatment, place it at 25°C for 8 hours and thaw it to obtain a milky white silk fibroin / sodium hyaluronate composite emulsion.
[0089] (2) Preparation of silk fibroin / sodium hyaluronate composite microspheres:
[0090] The composite emulsion was diluted 7 times with pure water, and then the organic solvent was removed at high temperature by spray drying (spray drying parameters were: air inlet temperature 150°C, liquid feed rate 10mL / min, fan frequency 20Hz), and pure and dry silk fibroin / sodium hyaluronate composite microspheres were collected.
[0091] (3) Preparation of silk fibroin / sodium hyaluronate composite microsphere gel:
[0092] The silk fibroin / sodium hyaluronate composite microspheres and sodium hyaluronate powder were dissolved in a sodium hydroxide solution with a mass concentration of 0.5% (the concentration of the silk fibroin / sodium hyaluronate composite microspheres was 35 mg / mL, and the concentration of the sodium hyaluronate was 70 mg / mL) to obtain a dissolving solution, and then 2 wt% of 1,4-butanediol diglycidyl ether was added to the dissolving solution. After the solution was stirred evenly, it was placed in a constant temperature environment at 40°C for a cross-linking reaction for 8 hours to finally form a gel.
[0093] Swelling properties of silk fibroin / sodium hyaluronate composite microsphere gel:
[0094] The silk fibroin microsphere / sodium hyaluronate composite microsphere gel was weighed in advance and recorded as W1. Then, the material was completely immersed in pure water and oscillated in a water bath at a constant temperature of 37°C for 24 hours. The material was taken out and rinsed with pure water for 3 times. The remaining water on the surface of the gel was removed with absorbent kitchen paper and weighed and recorded as W2.
[0095] The swelling rate was calculated according to N=(W2-W1) / W1×100%, and the swelling rate of the gel was calculated to be 36.6±5.1%, which is relatively low compared with pure sodium hyaluronate gel.
[0096] Degradation properties of silk fibroin / sodium hyaluronate composite microsphere gel:
[0097] The silk fibroin / sodium hyaluronate composite microsphere gel was swollen in PBS solution for 12 hours, and its wet weight after removing the surface water was weighed W1. Then, the swollen material was sterilized at 121°C for 8 minutes, and 2U / mL type I collagenase solution and PBS buffer (buffer pH value is 7.4) were added respectively. Then, it was placed in a 37°C constant temperature incubator for degradation, and the samples were taken out at 2h, 4h, 8h, 16h, 24h, 72h, 96h, 120h, and 144h to weigh its wet weight after removing the surface liquid W2, and the degradation solution was replaced once a day.
[0098] The remaining mass ratio is calculated according to the formula W2 / W1×100%, and the result is shown in Figure 4 ,from Figure 4 It can be seen that under the action of type I collagenase, the degradation rate of the gel is higher than that in PBS, indicating that the silk fibroin microsphere / sodium hyaluronate composite microsphere gel material is biodegradable.
[0099] The gel was placed in pure water for swelling twice, each time the amount of pure water used was 35 times the mass of the gel, and each swelling time was 5 hours; then the swollen gel was placed in a phosphate buffer solution (PBS solution) with an osmotic pressure of 300mOsmol / kg, and the contraction was strengthened three times, each time the amount of PBS solution used was 35 times the mass of the gel, and each strengthening time was 8 hours.
[0100] (4) Preparation of sterile silk fibroin / sodium hyaluronate composite microsphere gel:
[0101] The silk fibroin / sodium hyaluronate composite microsphere gel after strengthening was sieved with a 50 μm pore size sieve, and then filled into a prefilled syringe through a filling device, and then sterilized with wet heat at 121° C. for 8 minutes to obtain a sterile silk fibroin / sodium hyaluronate composite microsphere gel.
[0102] Example 3
[0103] (1) Preparation of silk fibroin / sodium hyaluronate composite emulsion:
[0104] Prepare 500 mL of a mixed solution of silk fibroin (average molecular weight 100 kDa) and sodium hyaluronate (average molecular weight about 1500 kDa) (the mixed solution contains 20 g of silk fibroin and 4 g of sodium hyaluronate), then add 80 mL of a mixed solution of propanol and isopropanol, mix well and place it in a -30°C environment for freezing and crystallization for 48 hours. After the freezing treatment, anneal it at -2°C for 12 hours, and then thaw it at room temperature to obtain a milky white silk fibroin / sodium hyaluronate composite emulsion.
[0105] (2) Preparation of silk fibroin / sodium hyaluronate composite microspheres:
[0106] The composite emulsion was diluted 6 times with pure water, and then the organic solvent was removed at high temperature by spray drying (spray drying parameters were: air inlet temperature 180°C, liquid feed rate 20mL / min, fan frequency 20Hz), and pure and dry silk fibroin / sodium hyaluronate composite microspheres were collected.
[0107] (3) Preparation of silk fibroin / sodium hyaluronate composite microsphere gel:
[0108] The silk fibroin / sodium hyaluronate composite microspheres and sodium hyaluronate powder were dissolved in a sodium hydroxide solution with a mass concentration of 0.5% (the concentration of the silk fibroin / sodium hyaluronate composite microspheres was 20 mg / mL and the concentration of sodium hyaluronate was 50 mg / mL) to obtain a dissolving liquid, and then 1wt% of 1,4-butanediol diglycidyl ether was added to the dissolving liquid, and the solution was stirred evenly and placed in a 55°C constant temperature environment for cross-linking reaction for 10 hours to finally form a gel. The gel was placed in pure water for swelling 3 times, each time the amount of pure water was 40 times the mass of the gel, and each swelling time was 6 hours; then the swollen gel was placed in a sodium chloride solution with an osmotic pressure of 350mOsmol / kg for contraction and strengthening 3 times, each time the amount of sodium chloride solution was 30 times the mass of the gel, and each strengthening time was 10 hours.
[0109] (4) Preparation of sterile silk fibroin / sodium hyaluronate composite microsphere gel:
[0110] The silk fibroin / sodium hyaluronate composite microsphere gel after strengthening was sieved with a 20 μm pore size mesh, then filled into a prefilled syringe through a filling device, and then sterilized with wet heat at 121° C. for 8 minutes to obtain a sterile silk fibroin microsphere / sodium hyaluronate composite microsphere gel.
[0111] Stability test of sterile silk fibroin / sodium hyaluronate composite microsphere gel:
[0112] The sterilized product was centrifuged (centrifugal force 4500g, centrifugal time 10 minutes), and no product stratification was observed (see Figure 5 (middle B).
[0113] Referring to the pushing force test method in YY / T 0962-2021 "Cross-linked Sodium Hyaluronate for Plastic Surgery", the pushing force of the product filled in the syringe was tested using a medical packaging physical properties tester to understand the actual conditions of the composite microsphere gel during use. The test found that when the pushing was smooth, the maximum pushing force was 20.35N, and the minimum value was 16.87N. The difference between the maximum and minimum values was very small, indicating that the pushing process was smooth and the average pushing force was about 18N.
[0114] Comparison Example
[0115] The silk fibroin / sodium hyaluronate composite microspheres prepared in step (2) of Example 3 are compounded with a non-cross-linked sodium hyaluronate solution, the osmotic pressure of the non-cross-linked sodium hyaluronate is 350mOsmol / kg, and the osmotic pressure regulator is sodium chloride. The ingredients of the compounded product are a silk fibroin / sodium hyaluronate composite microsphere concentration of 10mg / mL and a sodium hyaluronate concentration of 12mg / mL. Sieve with a 20μm pore size sieve, then fill into a prefilled syringe through a filling device, and after wet heat sterilization at 121°C for 8min, perform a centrifugation test (centrifugal force of 4500g, centrifugation time of 10 minutes), and it can be seen that the product has obvious stratification (see Figure 5 A in the middle, arrow points to the direction). This indicates that cross-linking the silk fibroin / sodium hyaluronate composite microspheres with the sodium hyaluronate gel can improve the stability of the system.
[0116] Example 4
[0117] (1) Preparation of silk fibroin / sodium hyaluronate composite emulsion:
[0118] Prepare 500 mL of a mixed solution of silk fibroin (average molecular weight 100 kDa) and sodium hyaluronate (average molecular weight about 1500 kDa) (the mixed solution contains 15 g of silk fibroin and 4 g of sodium hyaluronate), then add 30 mL of a mixed solution of methanol and ethanol, mix well and place it in a -35°C environment for freezing and crystallization for 36 hours. After the freezing treatment, anneal it at -4°C for 8 hours, and then thaw it at room temperature to obtain a milky white silk fibroin / sodium hyaluronate composite emulsion.
[0119] (2) Preparation of silk fibroin / sodium hyaluronate composite microspheres:
[0120] The composite emulsion was diluted 4 times with pure water, and then the methanol and ethanol were removed at high temperature by spray drying (spray drying parameters were: air inlet temperature 180°C, liquid feed rate 15mL / min, fan frequency 20Hz), and pure and dry silk fibroin / sodium hyaluronate composite microspheres were collected.
[0121] (3) Preparation of silk fibroin / sodium hyaluronate composite microsphere gel:
[0122] The silk fibroin / sodium hyaluronate composite microspheres and sodium hyaluronate powder were dissolved in a sodium hydroxide solution with a mass concentration of 1% (the concentration of the silk fibroin / sodium hyaluronate composite microspheres was 30 mg / mL and the concentration of sodium hyaluronate was 50 mg / mL) to obtain a dissolving liquid, and then 0.5wt% of 1,4-butanediol diglycidyl ether was added to the dissolving liquid, and the solution was stirred evenly and placed in a constant temperature environment at 37°C for cross-linking reaction for 24 hours to finally form a gel. The gel was placed in pure water for swelling 3 times, each time the amount of pure water was 30 times the mass of the gel, and each swelling time was 6 hours; then the swollen gel was placed in a sodium chloride solution with an osmotic pressure of 300mOsmol / kg for contraction and strengthening 3 times, each time the amount of sodium chloride solution was 30 times the mass of the gel, and each strengthening time was 10 hours.
[0123] (4) Preparation of sterile silk fibroin / sodium hyaluronate composite microsphere gel:
[0124] The silk fibroin / sodium hyaluronate composite microsphere gel after strengthening was sieved with a sieve with a pore size of 50 μm, and then filled into a prefilled syringe through a filling device, and then sterilized with wet heat at 115° C. for 30 minutes to obtain a sterile silk fibroin / sodium hyaluronate composite microsphere gel.
[0125] Example 5
[0126] (1) Preparation of silk fibroin / sodium hyaluronate composite emulsion:
[0127] Prepare 500 mL of a mixed solution of silk fibroin (average molecular weight 100 kDa) and sodium hyaluronate (average molecular weight about 1200 kDa) (the mixed solution contains 15 g of silk fibroin and 2.5 g of sodium hyaluronate), then add 50 mL of the mixed solution of ethanol, mix well and place it in a -20°C environment for freezing and crystallization for 48 hours. After the freezing treatment, anneal it at 0°C for 18 hours, and then thaw it at room temperature to obtain a milky white silk fibroin / sodium hyaluronate composite emulsion.
[0128] (2) Preparation of silk fibroin / sodium hyaluronate composite microspheres:
[0129] The composite emulsion was diluted 5 times with pure water, and then the ethanol was removed at high temperature by spray drying (spray drying parameters were: inlet air temperature 200°C, liquid feed rate 20mL / min, fan frequency 25Hz), and pure and dry silk fibroin / sodium hyaluronate composite microspheres were collected.
[0130] (3) Preparation of silk fibroin / sodium hyaluronate composite microsphere gel:
[0131] The silk fibroin / sodium hyaluronate composite microspheres and sodium hyaluronate powder were dissolved in 1% sodium hydroxide solution (the concentration of silk fibroin / sodium hyaluronate composite microspheres was 30 mg / mL and the concentration of sodium hyaluronate was 80 mg / mL), and then 2% 1,4-butanediol diglycidyl ether was added respectively. The solution was stirred evenly and placed in a constant temperature environment of 50°C for reaction for 24 hours to finally form a gel. The gel was placed in pure water for swelling 3 times, each time the amount of pure water was 50 times the mass of the gel, and each swelling time was 15 hours; then the swollen gel was placed in a phosphate buffer with an osmotic pressure of 320mOsmol / kgl for contraction and strengthening 3 times, each time the amount of sodium chloride solution was 30 times the mass of the gel, and each strengthening time was 15 hours.
[0132] (4) Preparation of sterile silk fibroin / sodium hyaluronate composite microsphere gel:
[0133] The silk fibroin microsphere / sodium hyaluronate composite microsphere gel after strengthening was sieved with a 50 μm pore size mesh, then filled into a prefilled syringe through a filling device, and then sterilized with wet heat at 121° C. for 8 minutes to obtain a sterile silk fibroin / sodium hyaluronate composite microsphere gel.
[0134] Silk fibroin / sodium hyaluronate composite microsphere gel cytotoxicity test:
[0135] It is carried out in accordance with the provisions of the MTT method in Appendix C of GB / T16886.5-2017 "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Test".
[0136] Sample preparation:
[0137] MEM complete medium: MEM medium without phenol red, containing 10% fetal bovine serum, 4 mmol / L glutamine, 100 IU / mL penicillin and 100 μg / mL streptomycin.
[0138] Sample group: The sterile silk fibroin / sodium hyaluronate composite microsphere gel of Example 5 was mixed with 0.9% sodium chloride injection at a volume ratio of 2:1, and the mixed solution was taken at a ratio of 0.2 g / mL, and the extraction medium was a serum-containing culture medium, and the extract was prepared at (37°C±1)°C and (24±2) h.
[0139] 100% test solution: 1mL extraction solution
[0140] 75% test solution: 0.75mL extraction solution + 0.25mL MEM complete medium
[0141] 50% test solution: 0.50mL extraction solution + 0.50mL MEM complete medium
[0142] 25% test solution: 0.25mL extraction solution + 0.75mL MEM complete medium
[0143] Positive control: 1 mL 20% DMSO: 0.2 mL DMSO + 0.8 mL MEM complete medium.
[0144] Negative control: 1 mL MEM complete medium.
[0145] Blank control: 2 mL MEM complete medium, treated with the same extraction conditions.
[0146] Each group was placed in a 96-well plate cultured with mouse fibroblasts, with 6 parallel samples each, and cultured in a 5% CO2, (37±1)°C incubator. After 24 hours, the cell morphological changes of each group were observed under a microscope, and then the cell survival rate of each test group (sample group, negative control group, positive control group) relative to the blank control group was determined by the MTT method.
[0147] The average absorbance values and survival rates of each test group are shown in Table 1:
[0148] Table 1 Cytotoxicity test results
[0149]
[0150]
[0151] Blank control OD 570b (The average optical density of the test sample) is 1.108, and the average value of the blanks in the left and right columns differs from the average value of all blanks by 1.828%, which meets the acceptance criteria.
[0152] The negative control and positive control were consistent with the expected reactions, and this experiment was established.
[0153] The survival rate of the test sample in 50% extract is higher than that in 100% extract, so this test is established.
[0154] The 100% test liquid survival rate of the sample is 78.77%, which is greater than 70%, and the silk fibroin / sodium hyaluronate composite microsphere gel has no cytotoxicity.
[0155] Silk fibroin / sodium hyaluronate composite microsphere gel intradermal reaction test:
[0156] The biocompatibility test of silk fibroin / sodium hyaluronate composite microsphere gel test solution was carried out in accordance with the requirements for intradermal reaction recommended in GB / T16886.10-2017 "Biological Evaluation of Medical Devices Part 10: Irritation and Skin Sensitization Tests".
[0157] The test sample was extracted in 0.9% sodium chloride injection (SC) and cottonseed oil (CSO) to prepare the extract of the test sample. The preparation process was as follows: take the sterile silk fibroin / sodium hyaluronate composite microsphere gel of Example 5, and extract the medium with 0.9% sodium chloride injection and cottonseed oil at a ratio of 0.2 g / mL; prepare the extract at (37°C±1)°C and (72±2)h, and prepare the control solution without adding the test sample in the same way. The test sample extract and the control solution were intradermally injected into both sides of the rabbit spine (for each extract), and the injection volume was 0.2mL per point. The reaction of each injection site was observed at 24h, 48h, and 72h after injection, and the tissue reaction score of erythema and edema of each injection site in each observation period was scored according to Table 2. The difference between the average score of the intradermal reaction of the test sample and the corresponding solvent control was calculated, and the results are shown in Tables 3 and 4.
[0158] Table 2 Intradermal reaction scoring standards
[0159]
[0160] Table 3 Intradermal reaction observation table (SC group)
[0161]
[0162] Table 4 Intradermal reaction observation table (CSO group)
[0163]
[0164]
[0165] As shown in Tables 3 and 4, the intradermal reaction observation of all test animals was normal. After the last observation, the final score difference of the intradermal reaction of the rabbits with the 0.9% sodium chloride injection (SC) extract of the product was 0.3, and the final score difference of the intradermal reaction of the rabbits with the cottonseed oil (CSO) extract was 0, both of which were not greater than 1.0. The test results met the requirements, and the silk fibroin / sodium hyaluronate composite microsphere gel had no intradermal reaction.
[0166] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a silk fibroin / sodium hyaluronate composite microsphere gel, characterized in that: The following steps are involved: Mixing a sodium hyaluronate solution, a silk fibroin solution and an organic solvent, freezing and crystallizing the resulting mixed solution and then thawing it to obtain a silk fibroin / sodium hyaluronate composite emulsion; spray drying the silk fibroin / sodium hyaluronate composite emulsion to obtain silk fibroin / sodium hyaluronate composite microspheres; The silk fibroin / sodium hyaluronate composite microspheres, sodium hyaluronate powder and alkaline solution are mixed until the sodium hyaluronate powder is completely dissolved to obtain a dissolved liquid; the dissolved liquid is mixed with a cross-linking agent to perform a cross-linking reaction to form a gel; The gel is placed in water for swelling, and then taken out and placed in a buffer solution for shrinkage and strengthening to obtain the silk fibroin / sodium hyaluronate composite microsphere gel.
2. The preparation method according to claim 1, characterized in that: After obtaining the silk fibroin / sodium hyaluronate composite microsphere gel, the method further includes sterilizing the silk fibroin / sodium hyaluronate composite microsphere gel to obtain a sterile silk fibroin / sodium hyaluronate composite microsphere gel.
3. The preparation method according to claim 1, characterized in that: The mass ratio of silk fibroin to sodium hyaluronate in the mixed solution is (3-7):
1.
4. The preparation method according to claim 1 or 3, characterized in that: The temperature of the freezing crystallization is -80 to -15°C, and the time of the freezing crystallization is 12 to 48 hours.
5. The preparation method according to claim 1, characterized in that: The spray drying conditions include: air inlet temperature of 100-200° C., feed rate of 5-30 mL / min, and fan frequency of 10-25 Hz.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the silk fibroin / sodium hyaluronate composite microspheres to the sodium hyaluronate powder is 1:(1.5-3); The concentration of the silk fibroin / sodium hyaluronate composite microspheres in the dissolving solution is 20-50 mg / mL; The mass concentration of alkali in the alkali solution is 0.01-2%; The alkali in the alkali solution is sodium hydroxide and / or potassium hydroxide.
7. The preparation method according to claim 1, characterized in that: The cross-linking agent includes 1,4-butanediol diglycidyl ether; the mass of the cross-linking agent is 0.1-5% of the mass of the dissolved liquid; The temperature of the cross-linking reaction is 37-65° C. and the time is 6-24 hours.
8. The preparation method according to claim 1, characterized in that: The buffer solution is a phosphate buffer solution or a sodium chloride solution, and the osmotic pressure of the buffer solution is 300-400 mOsmol / kg.
9. The silk fibroin / sodium hyaluronate composite microsphere gel prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention comprises sodium hyaluronate gel and silk fibroin / sodium hyaluronate composite microspheres which are cross-linked and distributed in the sodium hyaluronate gel.
10. Use of the silk fibroin / sodium hyaluronate composite microsphere gel according to claim 9 in the preparation of injections or gel dressings for cosmetic or medical purposes.
Citation Information
Patent Citations
Silk-fibroi and hyaluronic-acid (HA) composite gel for injection and preparation and application thereof
CN102836465A
Silk fibroin / HA (hyaluronic acid) composite microsphere freeze-dried powder carrying active ingredients as well as preparation method and application
CN106176281A
Emulsified cross-linked sodium hyaluronate gel microspheres for injection and preparation method thereof
CN111686664A
Preparation method of hyaluronic acid filling agent
CN113861458A
Silk fibroin composite gel for injection
CN113877001A
Cited By
Silk fibroin composite microsphere, gel, preparation method and application
CN122057079A